Community Figures' Perception Towards the Obligation of Halal Certification for Chicken Slaughterhouses - Dina Tama, Muhammad Rafli; El-Barqi, Muhammad Nur Sholeh (Islamic Economic Law Study Program, Faculty of Sharia Sultan Aji Muhammad Idris Samarinda Islamic State University, 2024)
This study discusses the perception of community leaders in Tanjung Perepat Village, Biduk Biduk District, towards chicken slaughterhouses that have not been halal certified. The researcher conducted this study to understand how community leaders in Tanjung Perepat Village, Biduk Biduk District, view chicken slaughterhouses lacking halal certification. The problem formulation for this study is: 1) What are the factors that cause chicken slaughterhouses in Tanjung Perepat Village, Biduk Biduk District, to not be halal certified?; 2) What are the perceptions of community leaders towards chicken slaughterhouses that have not been halal certified? This type of research is empirical research with a qualitative descriptive approach, namely research with field data as the main data source, such as interview results and observations. The study concluded that both internal and external factors caused the chicken slaughterhouses in Tanjung Perepat Village, Biduk Biduk District, to lack halal certificates. Internal factors are education, social, and social media. External factors include a lack of socialization, limited facilities, and difficulty accessing transportation. Interview findings reveal that community leaders in Tanjung Perepat Village, Biduk Biduk District, lack knowledge about the slaughterhouse's halal certification. This is because some of them are unaware that obtaining a halal certificate is solely necessary for packaged food and food ingredients.